Treatment of wet electrostatic precipitators wastewater by supercritical water oxidation - Tekbas, Aytug; Bektaş, Nihal; Tekbas, Mesut; Gurbulak, Ercan; Yüksel, Ebubekir (Taylor & Francis Inc, 2022)
The most commonly used method for treating gas emissions generated during the drying process in chipboard production plants is the Wet Electrostatic Precipitator (WESP). The wastewater generated from the WESP process is considered hazardous due to high pollutants loads and cannot be treated efficiently using conventional treatment methods, such as chemical and biological treatment, sedimentation, and various separation processes. Therefore, there is an urgent need to investigate a novel and efficient treatment method for WESP wastewater. Supercritical water oxidation (SCWO) has recently gained attention as a powerful technique that can remove organic pollutants from wastewater in a short time. In this study, the removal of pollutants from real WESP wastewater was investigated using the SCWO process. The effects of operating conditions; oxidation rate, reaction temperature, and process reaction time, were studied under different experimental conditions. For the SCWO process, optimum conditions 99%, the reaction time of 166 seconds, oxidant ratio of 1.78 and 600 degrees C were determined for 95% yield of total organic carbon (TOC) and total nitrogen (TN). The overall results showed that the TOC and TN removal efficiencies increased with the increase of temperature, oxidant dosage, and reaction time. The result from this study indicated that SCWO is a promising and innovative technique for the treatment of WESP wastewater.
Keywords: Box-Behnken design; chipboards plants; supercritical water oxidation; wet electrostatic precipitators; WESP wastewater